Rulers and Realms in Medieval Iberia, 711-1492 - Flood, Timothy M., 1943- (McFarland & Company, Inc., Publishers, 2019)
"The Muslim conquest of Iberia in 711 began nearly eight centuries of struggle for control of the peninsula. The invaders quickly achieved military supremacy, but political dominance was less complete. Within a few years, a small band of Christian rebels defied Muslim authority, establishing their own ruling class in the northern mountains of Asturias."--Provided by publisher.